Chemistry and physics of dopants embedded in helium droplets. Issue 4 (16th May 2021) - Albertini, Simon; Gruber, Elisabeth; Zappa, Fabio; Krasnokutski, Serge; Laimer, Felix; Scheier, Paul
Abstract: Helium droplets represent a cold inert matrix, free of walls with outstanding properties to grow complexes and clusters at conditions that are perfect to simulate cold and dense regions of the interstellar medium. At sub‐Kelvin temperatures, barrierless reactions triggered by radicals or ions have been observed and studied by optical spectroscopy and mass spectrometry. The present review summarizes developments of experimental techniques and methods and recent results they enabled.